ANTI-INFLAMMATORY AND ANALGESIC ACTIVITY OF RETICULATED PYTHON FAT OIL (MALAYOPYTHON RETICULATUS) IN VIVO EVALUATION - Hajrah, Hajrah; Febriani, Dina Arindha; Indriyanti, Niken (Indonesian Journal of Pharmaceutical Science and Technology, 2024)
Empirically, python fat oil (Malayopython reticulatus) is used by local people in Miau Baru, Kongbeng, East Kalimantan to treat swelling and inflammation. The purpose of this study was to determine the physical characteristics, anti-inflammatory, and analgesic activities of the python fat oil in reducing pain and inflammation. The methods that are used for determining physical characteristics are organoleptic test, density test, viscosity test, pH test, and refractive index test. The method that is used for determining anti-inflammatory activities is the paw edema method, which is induced by lambda carrageenan, and for analgesic activities using the hot plate method. The results obtained are that python oil has a yellow-orange color, a rancid odor, and has a bland taste, has a density of 0.870 g/mL with a pH of 4.1. The viscosity of the python fat oil is 2.2 Pa.s with a refractive index of 1.463. The percentage of edema formed at 5% concentration was 0.33%, 10% concentration was 0.43%, and 15% concentration was 0.25%. A recent increase in survival time in analgesic testing with a 5% concentration of 4.44%, a 10% concentration of 3.87%, and a 15% concentration of 3.11%. It was concluded that python fat oil has anti-inflammatory and analgesic activity.